Strategic appeals and audience alignment in government short videos: A corpus-based analysis - Hong Zhang (PLoS ONE, 2026)
This study examines how government short videos construct persuasive discourse through rhetorical strategies, using the Douyin account Meili Zhejiang as a case study. Drawing on audience-identification theory and Aristotle’s three rhetorical appeals (ethos, pathos, logos), it develops a text-centered rhetorical-computational framework that combines corpus-based methods and rhetorical analysis. The dataset covers 360 top-liked videos posted over one year and all publicly visible comments, with exact-text duplicates removed. Python-based lexical and sentiment analyses, together with concordance inspection in AntConc, are used to trace how persuasive appeals are realized in the textual dimension of the videos and how they align with audience orientations. Results show that pathos predominates (44.77%), expressed through affect-rich language of familial warmth, collective pride, encouragement, and urgency. Ethos (28.33%) is built through institutional roles and localized references, often strengthened by citizen voices, while logos (26.89%) appears in factual and quantifiable expressions that ground emotional and ethical claims. Sentiment in the associated comment corpus shows a generally positive tendency (56.7%), consistent with the audience profile and the rhetorical configuration identified in the corpus. The study offers a corpus-assisted rhetorical approach to analyzing persuasion in platform-mediated governance and highlights how communicative effectiveness is shaped by a calibrated construction of appeals aligned with audience dispositions in short-video communication.